PWE-289 Critical illness early warning scores retain accuracy in patients with liver disease—an analysis of 182 000 inpatient observation sets. (28th May 2012) - Hydes, T; Schmidt, P; Smith, G B; Prytherch, D; Aspinall, R J
Abstract : Introduction: Aggregate weighted track and trigger systems (AWTTS) can identify critically ill patients at high risk of mortality. However, these scores use features of the Systemic Inflammatory Response Syndrome (SIRS) that may be altered in liver disease such as resting tachycardia and hypotension secondary to hyperdynamic circulation, blunted pyrexial response or hyperventilation due to encephalopathy. These scores have not been evaluated in patients with liver disorders. We therefore examined whether a range of AWTTS, including the VitalPac Early Warning Score (ViEWS), retain accuracy in liver disease. Methods: Clinical observations were recorded on a computerised database (VitalPac) for all admissions between July 2006 and April 2011 in a large hospital serving a population of 650 000. Adults assigned International Classification of Diseases (ICD-10) codes for liver disease, either as primary or comorbid diagnosis, were identified. ViEWS scores of 0–19 1 were allocated to all vital sign sets. Each set contained: date/time, pulse, blood pressure, respiration, temperature, neurological status using either the Alert-Verbal-Painful-Unresponsive scale or Glasgow Coma Score, pulse oximetry and use of supplemental oxygen. Datasets were analysed with respect to number of patients needed to be seen by a doctor if escalation occurred at that score and inpatient mortality within 24 h. Results: We identified 44 328 observation sets for patients with a primary liver diagnosis (PLD) code of which 519 (1.17%) were followed by death within 24 h. For those with a non-primary liver diagnosis (NPLD) 138 217 observations were made and 1157 (0.84%) resulted in death. There were no differences at any ViEWS score in the prediction of 24-h mortality and number needed to be seen for patients assigned a PLD or NPLD, compared to all adult hospital admissions (Abstract PWE-289 figure 1). The area under the receiver-operating characteristics curve (95% CI) was 0.886 for all patients and 0.888 and 0.883 for those with PLD and NPLD respectively. Conclusion: Using an electronic database of all clinical observations and diagnostic codes, we found the accuracy of predicting death within 24 h was retained in the presence of liver disease regardless of primary or secondary diagnosis. We have now expanded this work to include analysis of 34 additional AWTTS scores and distinct clinical presentations of hepatic disorders. Competing interests: T Hydes: None declared, P Schmidt Shareholder with: Director of a company with a minority shareholding in the development of Learning Clinic software, G Smith: None declared, D Prytherch Shareholder with: Spouse holds shares in the Learning Clinic software development company, R Aspinall: None declared. Reference: 1. Prytherch DR, Smith GB, Schmidt PE, et al. ViEWS—Towards a national early warning score for detecting adult inpatient deterioration. Resuscitation 2010;81 :932–7.